2002
DOI: 10.1063/1.1427069
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced electronic energy transfer from v=0 of the E(0g+) ion-pair state in I2: Collisions with He and Ar

Abstract: The electronic energy transfer pathways that occur following collisions between I 2 in the E ion-pair electronic state ͑vϭ0, Jϭ55͒ and He and Ar atoms have been determined. The nearby D, DЈ, and ␤ ion-pair states are populated, but with relative branching ratios that vary with the rare gas collision partner. In He/I 2 collisions, the D state is preferentially populated, while Ar/I 2 collisions preferentially populate the ␤ electronic state. Bimolecular rate constants and effective hard sphere collision cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 46 publications
2
50
2
Order By: Relevance
“…4 has an additional contribution from a bimodal series of peaks with maxima near 262.2 and 274.5 nm, indicative of emission from v D = 1. 10,12 Whereas He and Ar collisions produced similar vibrational state distributions in the IP pair states of iodine, our present results show markedly different dynamics between collisions of the Rgs with bromine. Our spectral fits allow for the emission from v D =0-4 and the small, additional peaks in the bottom half of Fig.…”
Section: A E \ D Transfermentioning
confidence: 49%
See 2 more Smart Citations
“…4 has an additional contribution from a bimodal series of peaks with maxima near 262.2 and 274.5 nm, indicative of emission from v D = 1. 10,12 Whereas He and Ar collisions produced similar vibrational state distributions in the IP pair states of iodine, our present results show markedly different dynamics between collisions of the Rgs with bromine. Our spectral fits allow for the emission from v D =0-4 and the small, additional peaks in the bottom half of Fig.…”
Section: A E \ D Transfermentioning
confidence: 49%
“…[10][11][12][13] Double resonance excitation prepares bromine molecules in a single vibrational level of the E electronic state. [10][11][12][13] Double resonance excitation prepares bromine molecules in a single vibrational level of the E electronic state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…D0 þ u ð 3 P 2 Þ transfer is mainly by collisions rather than by ASE. Fecko et al [17] carried out a detailed study of the collisional transfer from E0 þ g ð 3 P 2 Þ (v = 0) using He, under non-ASE conditions, and showed that (v = 0-3) of the D0 þ u ð 3 P 2 Þ state were populated to a similar degree.…”
Section: The Effect Of a Collision Partner On Ase Transfermentioning
confidence: 93%
“…X0 þ g (aa) emission is observed. Although Fecko et al [17] did not use Xe as a collision partner, they did observe an increase in the efficiency of the E0 þ g ð 3 P 2 Þ ! D 0 2 g ð 3 P 2 Þ/b1 g ( 3 P 2 ) transfer relative to the E0 þ g ð 3 P 2 Þ !…”
Section: The Effect Of a Collision Partner On Ase Transfermentioning
confidence: 94%